Bonding Characteristics of Macrosynthetic Fiber in Latex-Modified Fiber-Reinforced Cement Composites as a Function of Carbon Nanotube Content - Ji-Hong Jean; Chan Yu; Chan-Gi Park (International Journal of Polymer Science)
The effect of carbon nanotube content (0, 0.5, 1.0, 1.5, and 2.0% of the cement weight) on the bonding properties of macrosynthetic fiber in latex-modified hybrid fiber cement-based composites (LMHFRCCs) was evaluated. The slump value, compressive strength, and bonding strength were measured for each LMHFRCC. As the carbon nanotube content increased to 1.5%, the bonding properties of the macrosynthetic fiber improved. However, the bonding performance deteriorated at a carbon nanotube content of 2.0%. A decrease in the fluidity of the mix negatively affected the dispersion of the nanotubes in the LMHFRCCs. The addition of carbon nanotubes also affected the relative bonding strength independently of the improvement in compressive strength. Microscopic analysis of the macrosynthetic fiber surfaces was used to understand changes in the bonding behavior.